NASH game and mixed H2/H∞ control - de, Helenice [UNESP]; Sales, Roberto M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1997)
In this work a Nonzero-Sum NASH game related to the H2 and H∞ control problems is formulated in the context of convex optimization theory. The variables of the game are limiting bounds for the H2 and H∞ norms, and the final controller is obtained as an equilibrium solution, which minimizes the `sensitivity of each norm' with respect to the other. The state feedback problem is considered and illustrated by numerical examples.
Keywords: Feedback; Game theory; Optimization; Problem solving; Convex optimization problem; Optimal control systems